Highly-sensitive phase-interrogated RI sensor based on twin-core fiber with inherent noise suppression. (September 2019) - Xia, Feng; Hu, Hai-feng; Zhao, Yong
Highlights: We propose a highly-sensitive phase-interrogated RI sensor based on twin-core fiber with inherent noise suppression. It is the first time that optical fiber sensing structure is combined with digital holography technology, which works as the phase interrogation method, for measuring environmental parameters. The background signal is reduced to 1/25 of the original noise level by using phase subtraction method within a single measurement. Experimental results show that a short response time of about 13 s and a high sensitivity of about 835 rad/refractive index unit (RIU) are obtained. The achieved high sensitivity is about 47 times higher than the sensitivity of a refractive index plasmonic sensor realized by enabling its quadrupole resonance in phase interrogation (17.46 rad/RIU). Abstract: In this work, we propose a highly-sensitive phase-interrogated RI sensor based on twin-core fiber with inherent noise suppression. This is the first time that optical fiber sensing structure is combined with digital holography technology, which works as the phase interrogation method, for measuring environmental parameters. The proposed system consists of a Mach–Zehnder interferometer formed by interference between the reference Gauss beam and the sensing dual-beam from the twin-core fiber (TCF). In the sensing optical path, a non-core fiber (NCF) and TCF offset splicing structure works as the differential fluid RI sensing element, which provides the capability of suppressing background signal by calculating the phase difference between the two cores of the TCF. This simple and practical phase subtraction method realizes direct background subtraction within a single measurement and reduces the background signal to 1/25 of the original noise level. The fluid is continuously introduced into a fluid tube in which the sensing fiber is installed to realize in-line measurement of fluid RI. Experimental results show that a short response time of about 13 s and a high sensitivity of about 835 rad/refractive index unit (RIU) are obtained. The high sensitivity benefits from direct interaction between light path and fluid, which is about 47 times higher than the sensitivity of a refractive index plasmonic sensor realized by enabling its quadrupole resonance in phase interrogation (17.46 rad/RIU). This scheme will find many applications in little sample consumption and high sensitivity required analytical measurement owing to its merits of high sensitivity, little sample consumption, fast response, and inherent background noise suppression.